Adolescent Social Defeat Induced Alterations in Social Behavior and Cognitive Flexibility in Adult Mice: Effects of Developmental Stage and Social Condition - Zhang, Fan; Yuan, Sanna; Shao, Feng; Wang, Weiwen (Frontiers in Behavioral Neuroscience, 2016)
Negative social experiences during adolescence increase the risk of psychiatric disorders in adulthood. Using “resident-intruder” stress, the present study aimed to investigate the effects of adolescent social defeat on emotional and cognitive symptoms associated with psychiatric disorders during adulthood and the effects of the developmental stage and social condition on this process. In experiment 1, animals were exposed to social defeat or manipulation for 10 days during early adolescence (EA, PND 28-37), late adolescence (LA, PND 38-47), and adulthood (ADULT, PND 70-79) and then singly housed until the behavioral tests. Behaviors, including social avoidance of the defeat context and cortically mediated cognitive flexibility in an attentional set-shifting task (AST), were assessed during the week following stress or after 6 weeks during adulthood. We determined that social defeat induced significant and continuous social avoidance across age groups at both time points. The mice that experienced social defeat during adulthood exhibited short-term impairments in reversal learning on the AST that dissipated after 6 weeks. In contrast, social defeat during EA but not LA induced a delayed deficit in extra-dimensional set-shifting in adulthood but not during adolescence. In experiment 2, we further examined the effects of social condition (isolation or social housing after stress) on the alterations induced by social defeat during EA in adult mice. The adult mice that had experienced stress during EA exhibited social avoidance similar to the avoidance identified in experiment 1 regardless of the isolation or social housing after the stress. However, social housing after the stress ameliorated the cognitive flexibility deficits induced by early adolescent social defeat in the adult mice, and the social condition had no effect on cognitive function. These findings suggest that the effects of social defeat on emotion and cognitive function are differentially affected by the developmental stage and social condition. EA may comprise a particularly sensitive developmental period in which social defeat may produce a delayed impairment in cognitive flexibility during adulthood, and the social condition following stress appears to play an important intermediary role in the development of these cognitive deficits.